2018
DOI: 10.1007/s11356-018-2628-4
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous removal of NO and SO2 from flue gas using vaporized H2O2 catalyzed by nanoscale zero-valent iron

Abstract: To remove NO and SO from flue gas simultaneously, a heterogeneous catalytic oxidation system was developed with the nanoscale zero-valent iron (nZVI), vaporized HO, and sodium humate (HA-Na) acting as the catalyst, oxidant, and absorbent, respectively. The experimental results indicated that the desulfurization was mainly influenced by the absorption, and the denitrification was significantly affected by the catalytic oxidation parameters. Under the optimal conditions, the simultaneous removal efficiencies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Relevant research ,, showed that a rise of the temperature would reduce the solubility of hydrogen sulfide in the reaction solutions, which was not conducive to the hydrogen sulfide removal. Furthermore, some results indicated that chemical reactions could be enhanced by elevating the temperature, which would strengthen the hydrogen sulfide removal. However, for the photo-Fenton reaction process, free radical oxidation plays a dominant role for the hydrogen sulfide removal.…”
Section: Resultsmentioning
confidence: 99%
“…Relevant research ,, showed that a rise of the temperature would reduce the solubility of hydrogen sulfide in the reaction solutions, which was not conducive to the hydrogen sulfide removal. Furthermore, some results indicated that chemical reactions could be enhanced by elevating the temperature, which would strengthen the hydrogen sulfide removal. However, for the photo-Fenton reaction process, free radical oxidation plays a dominant role for the hydrogen sulfide removal.…”
Section: Resultsmentioning
confidence: 99%
“…[8] Thus, the Fenton-like reaction with * OH radicals from H 2 O 2 decomposition over heterogeneous catalysts would be effective and feasible for NO-oxidation. [9] Hematite, [10] hematite doped alumina, [11] zero-valent iron, [12] ferric sulfate, [7] Y-Fe 2 O 3 @Fe 3 O 4 , [13] Fe 2.5 M 0.5 O 4 [14] and Fe 2 (MoO 4 ) 3 [15] have been developed for denitrification by catalytic H 2 O 2 -producing * OH radicals, and the high NO-removal conversions were observed. However, for those catalysts, the relative low surface area might impose low utilization of active sites.…”
Section: Introductionmentioning
confidence: 99%